2019
DOI: 10.2807/1560-7917.es.2019.24.10.1800174
|View full text |Cite
|
Sign up to set email alerts
|

Influenza C virus in pre-school children with respiratory infections: retrospective analysis of data from the national influenza surveillance system in Germany, 2012 to 2014

Abstract: IntroductionRecent data on influenza C virus indicate a possible higher clinical impact in specified patient populations than previously thought.AimWe aimed to investigate influenza C virus circulation in Germany.MethodsA total of 1,588 samples from 0 to 4 year-old children presenting as outpatients with influenza-like illness (ILI) or acute respiratory infection were analysed retrospectively. The samples represented a subset of all samples from the German national surveillance system for influenza in this age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Gouarin et al reported a peak of disease in France in winter-spring of 2005 while little ICV was detected in the two following seasons [101]. Fritsch et al noted a similar seasonal pattern in Germany, with a peak of ICV detection in fall-winter-spring of 2012-2013, with minimal detection in the seasons preceding and following [99]. Thielen et al describe a winter-spring outbreak of 51 cases in the US during 2013-2015 while in the seasons before and after only 2 and 8 cases were reported, respectively [103].…”
Section: Seasonalitymentioning
confidence: 95%
See 2 more Smart Citations
“…Gouarin et al reported a peak of disease in France in winter-spring of 2005 while little ICV was detected in the two following seasons [101]. Fritsch et al noted a similar seasonal pattern in Germany, with a peak of ICV detection in fall-winter-spring of 2012-2013, with minimal detection in the seasons preceding and following [99]. Thielen et al describe a winter-spring outbreak of 51 cases in the US during 2013-2015 while in the seasons before and after only 2 and 8 cases were reported, respectively [103].…”
Section: Seasonalitymentioning
confidence: 95%
“…A Japanese longitudinal study of 190 ICV isolates collected over seven years found that nearly all were <6 years old, with the highest rates of infection in children 1-2 years old [60]. Rates of detection of ICV in outpatient or hospitalized children with acute respiratory illness have ranged from 0.7-10% in studies from Australia, Canada, Cuba, India, Italy, Japan, Nigeria, Peru, Scotland, and Spain [1,12,20,61,63,68,70,[91][92][93][94][95][96][97][98][99][100][101][102]. Most of these studies found higher rates of ICV infection in younger children.…”
Section: Icv In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Evolutionary tree analyses have revealed that six antigenic lineages of influenza C virus diverged by approximately 1980 [ 5 , 34 ]. Although the C/Sao Paulo lineage and the C/Kanagawa lineage are now circulating worldwide [ 2 , 3 , 18 , 19 , 35 , 36 ], antigenic cross-reactivity between the C/Ann Arbor/1/50 (C/Taylor lineage) and recent isolates in Japan has been still confirmed [ 19 ]. We investigated whether the stable antigenicity of influenza C virus relates to the functional constraints on variation in the antigenic region of the HE glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, quantitative real time-polymerase chain reaction (qPCR) is a standard method where a fluorescent signal is coupled with DNA polymerase chain reaction for quantification of DNA [ 2 , 3 , 4 , 5 , 6 ]. Though this method affords the detection of the presence of 1–10 copies/mL of DNA sample, PCR is still restricted to professional laboratories due to the need for specialized instrumentation [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%